2019
DOI: 10.34044/j.anres.2019.53.6.03
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress and Acacia seyal biochar effects on sorghum gas exchange and yield: A greenhouse experiment

Abstract: Article Info AGRICULTURE AND NATURAL RESOURCESDrought is the controlling abiotic stress factor affecting crop production in dryland environments and exposes millions of people to food insecurity in Africa and Asia. Although sorghum is drought tolerant, it is not sufficiently known if biochar can reduce drought-related losses in yields in clay soils for this particular crop. The stomatal morphology and gas exchange responses were investigated of a sorghum cultivar, 'Wad Ahmed' (widely grown throughout Sudan and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Biochar is another promising additive that can mitigate the adverse effects of drought on plant growth and productivity, e.g., sorghum 14 , maize 15 and wheat 2 , 16 . This might take place via (I) increasing soil water retention, hence reducing soil irrigation demands 17 , (II) increasing nutrient use efficiency 18 , (III) stimulating auxin, gibberellin and brassinosteroids regulation 19 and (IV) increasing plant chlorophyll content 20 , stomatal conductance, cytotoxicity and leaf K + content 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is another promising additive that can mitigate the adverse effects of drought on plant growth and productivity, e.g., sorghum 14 , maize 15 and wheat 2 , 16 . This might take place via (I) increasing soil water retention, hence reducing soil irrigation demands 17 , (II) increasing nutrient use efficiency 18 , (III) stimulating auxin, gibberellin and brassinosteroids regulation 19 and (IV) increasing plant chlorophyll content 20 , stomatal conductance, cytotoxicity and leaf K + content 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends were also observed by Gavil et al (2019), who reported that an edaphic application of 1.25% (w/w) BC significantly increased the dry (35%) and fresh (27%) matter yields compared to the control (0% BC) in soybean plants with and without water stress. Deng et al (2019) also concluded that the benefits of BC application on plant growth in environments with water stress were due to an increase in the water retention capacity of the soil and an increase in the soil carbon content resulting from the dose of BC used. Additionally, BC application can optimize root length, root surface area, and root density and improve root cell viability, causing the root system to be a key pathway regulating aboveground plant growth under deficit irrigation conditions (Zhang et al, 2023) UAE and Kr also increased in RI plants, and B8.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Several studies have shown that using sorghum as a substitute for maize has varied effects, some being positive regarding performance, while other experiments produced negative results (Torres et al, 2013;Fagundes et al, 2017;Saleh et al, 2019). Sorghum plants have the advantage of being able to grow under dry and hot climatic conditions (Deng et al, 2019;Emendack et al, 2021). In response to global warming, sorghum has become a plant that can be adaptive to future climate change, so it is necessary to maximize its use, including for feed ingredients.…”
Section: Introductionmentioning
confidence: 99%